Informed consent in artificial nutrition and hydration: Ethical, legal, and clinical considerations - Lacasella, Giorgia Viola (Progress in Nutrition, 2025)
This article addresses the complex issue of informed consent in the context of Artificial Nutrition and Hydration (ANH). It explores how physicians should act when patients are unable to provide valid consent and whether explicit, legally prescribed consent is necessary or if presumed consent can be inferred from the patient’s lifestyle, values, and beliefs. The necessity of detailed patient information and the evolution of the doctor-patient relationship from a paternalistic model to one recognizing patient autonomy are discussed. The article emphasizes that ANH should be administered based on informed consent, except in exceptional urgent cases where presumed consent is applicable. Ethical and legal responsibilities of physicians in ensuring clear and comprehensible information for informed decision-making are highlighted. The article concludes that adherence to guidelines should be carefully considered and contextualized, ensuring that therapeutic choices respect the patient’s dignity and autonomy. This multidisciplinary approach, involving ethicists, legal experts, and family members, is essential for decisions made in the best interest of the patient.